Plant source pea starch deodorizing low-dust cat litter and preparation method thereof
By using natural pea starch and porous pea starch, combined with a composite deodorizing component consisting of leopard cyclodextrin, persimmon tannin, and sodium citrate buffer, the problem of existing cat litter being heavy, dusty, having poor deodorizing effect, inconvenient to transport, and having insufficient granule grinding, structural stability, and deodorizing capacity is solved. This achieves the effect of fast water absorption and clumping, intact wet clumps, less dust, and good deodorizing effect.
Patent Information
- Application Number
- CN202611345373.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-11-03
AI Technical Summary
Existing cat litter has problems such as being heavy, inconvenient to transport, producing a lot of dust, having poor deodorizing effect, being prone to wear and tear on the granules, and having a slow rate of water absorption and clumping. In addition, the uneven dispersion of compound deodorizing components affects the effectiveness of use.
This product is made from plant-derived pea starch, which is based on natural pea starch and porous pea starch. It is combined with pea fiber and compound deodorizing components. By combining β-cyclodextrin, persimmon tannin and sodium citrate buffer components and using thermomechanical modification, the resulting granular structure has stability and deodorizing ability.
It improves the water absorption and clumping speed and wet clumping integrity of cat litter, reduces dust generation, enhances the persistence of deodorization and the toughness of the granules, improves user comfort and environmental adaptability, and reduces the stability of dust-generating particles.
Smart Images

Figure CN123023558A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of pet product technology, specifically relating to a plant-derived pea starch deodorizing and low-dust cat litter and its preparation method. Background Technology
[0002] Cat litter is a common pet product used to absorb the excrement of cats and wrap up solid excrement. Its performance usually involves aspects such as water absorption speed, clumping strength, deodorization effect, granule abrasion resistance, and dust generation.
[0003] Currently, the most common cat litters on the market include bentonite cat litter and plant-based cat litter. Bentonite cat litter has a certain ability to absorb water and clump, but it is mainly made of mineral materials and usually has problems such as being heavy, inconvenient to transport and dispose of, easily generating dust during use, and being difficult to degrade naturally after use. Cat litter dust can also adhere to cat paws, cat hair, and the area around the litter box, affecting the cleanliness of the environment.
[0004] Plant-based cat litter typically uses soybean residue, plant fiber, starch, or other plant-derived materials as its main raw materials, and is characterized by its relatively light weight and high proportion of plant-based ingredients. However, existing plant-based cat litter may still have issues such as loose or brittle granules, and is prone to wear and tear during transportation and scratching by cats. Some plant-based cat litter hydrates and binds slowly after absorbing urine, and the resulting wet clumps are easily loose or broken, making them difficult to clean completely.
[0005] Furthermore, to improve the deodorizing performance of cat litter, existing products typically add adsorbents, plant extracts, or acid-regulating materials directly. These functional additives are usually small in particle size, and direct mixing can easily lead to uneven dispersion, localized agglomeration, and shedding from the particle surface. This not only affects the utilization efficiency of the deodorizing components but may also increase the amount of free powder in the cat litter. The effectiveness of single deodorizing components in treating ammonia, amine, sulfur-containing, and other volatile odors in urine is also limited, making it difficult to simultaneously achieve both initial deodorizing effect and sustained deodorizing capability. Summary of the Invention
[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide a plant-derived pea starch deodorizing and dust-reducing cat litter and its preparation method.
[0007] The technical objective of this invention is achieved through the following technical solution: The first aspect of this invention is to provide a plant-derived pea starch deodorizing and dust-reducing cat litter, which, based on a dry basis total mass of 100 parts, comprises the following raw materials: 75-95 parts of starch-based component, 2-22 parts of pea fiber, and 3-5 parts of composite deodorizing component; the mass parts of each raw material are selected within the above range, and the sum of the mass parts of the starch-based component, pea fiber, and composite deodorizing component is 100 parts; wherein, the starch-based component includes at least natural pea starch and porous pea starch, and selectively includes pregelatinized pea starch; the composite deodorizing component is composed of β-cyclodextrin, persimmon tannin, and a citric acid-sodium citrate buffer component.
[0008] Preferably, based on a total mass of 100 parts of starch-based components, the composition includes: 72-95 parts of natural pea starch, 0-18 parts of pregelatinized pea starch, and 5-10 parts of porous pea starch; the sum of the mass parts of the natural pea starch, pregelatinized pea starch, and porous pea starch is 100 parts.
[0009] Preferably, the median particle size D of the porous pea starch is... 50 The surface area is 20–45 μm, and the specific surface area measured by nitrogen adsorption BET method is 1.0–3.5 m². 2 / g, with an oil absorption rate of 90%–160%.
[0010] Preferably, the mass ratio of the porous pea starch to the composite deodorizing component is 1:0.4 to 1.0.
[0011] The natural pea starch serves as the main absorbent matrix of the cat litter granules, absorbing liquids and forming the granule skeleton. When the starch-based component contains pregelatinized pea starch, the pregelatinized pea starch enhances the hydration rate and wet adhesion strength of the cat litter granules upon contact with liquids. The porous pea starch loads and fixes the composite deodorizing components, dispersing them within the cat litter granules. The pea fiber helps regulate the internal structure and liquid permeability of the cat litter granules and contributes to improving granule toughness.
[0012] Preferably, the total mass of the composite deodorizing component is 100 parts, and its composition includes: 50-75 parts of β-cyclodextrin, 10-25 parts of persimmon tannin, and 15-30 parts of citric acid-sodium citrate buffer component; the sum of the mass parts of β-cyclodextrin, persimmon tannin, and citric acid-sodium citrate buffer component is 100 parts.
[0013] Preferably, in the citric acid-sodium citrate buffer component, the mass ratio of citric acid to sodium citrate is 1:0.5 to 2.5.
[0014] The β-cyclodextrin is used to encapsulate volatile organic odor molecules produced by cat excrement; the persimmon tannin is used to adsorb, complex, or fix amines and sulfur-containing odor substances; the citric acid-sodium citrate buffer component is used to adjust the local acid-base environment after the cat litter absorbs urine, increase the proportion of ammonia in the form of ammonium ions, and reduce the release of gaseous ammonia. At least a portion of the composite deodorizing components are loaded onto the pores and surface of the porous pea starch to form a loaded composite deodorizing material.
[0015] Preferably, in addition to the above-mentioned 100 parts of basic raw materials, preservatives acceptable to pet products may be added to improve the stability of cat litter during storage. The type and amount of such preservatives do not constitute essential technical features of the present invention.
[0016] A second aspect of the present invention is to provide a method for preparing plant-derived pea starch deodorizing and dust-reducing cat litter, specifically comprising the following steps: S1: β-cyclodextrin, persimmon tannin, and citric acid-sodium citrate buffer components are mixed with water to prepare a composite deodorizing dispersion; the composite deodorizing dispersion is added to porous pea starch for loading treatment, so that the composite deodorizing components at least partially enter the pores of the porous pea starch and adhere to the surface of the porous pea starch; after the loading treatment is completed, drying and depolymerization are performed to obtain a loaded composite deodorizing material; S2: When the amount of pregelatinized pea starch in the starch-based component is greater than 0 parts, a portion of the pregelatinized pea starch is reserved for step S4; when the amount of pregelatinized pea starch is 0 parts, a portion of the natural pea starch is reserved for step S4; the remaining starch raw materials, pea fiber, and the loaded composite deodorizing material obtained in step S1 are mixed to obtain an initial mixture; water is added according to the actual moisture content of the initial mixture and mixing continues to make the raw materials evenly dispersed to obtain a mixed base material for granulation. The mixed base material is kept in a loose powder or loose particle state and does not form wet lumps, soft materials, or slurry. S3: The mixed base material obtained in step S2 is fed into a roller granulator and granulated under heating and roller pressure to compact the mixed base material into initial cat litter particles. S4: Prepare a starch coating solution from the pea starch reserved in step S2, and apply the starch coating solution evenly to the surface of the initial cat litter particles obtained in step S3, so that the starch component is mainly concentrated on the outside of the cat litter particles, resulting in surface-coated particles; wherein, when the reserved pea starch is pregelatinized pea starch, it is mixed with water to prepare the starch coating solution; when the starch-based component does not contain pregelatinized pea starch, the reserved natural pea starch is mixed with water and heated to gelatinize to prepare the starch coating solution; S5: The surface-coated particles obtained in step S4 are dried at low temperature to solidify the surface coating and reduce the moisture content of the cat litter particles; after drying, they are cooled and sieved to remove unformed fine powder, broken particles and particles that do not meet the size requirements, so as to obtain plant-derived pea starch deodorizing and dust-free cat litter.
[0017] Preferably, in step S1, the composite deodorizing dispersion is added in batches to the continuously stirred porous pea starch by spraying, so as to avoid excessive local addition of liquid causing the porous pea starch to clump. Preferably, in step S1, the mass ratio of water to the composite deodorizing component in the composite deodorizing dispersion is 2 to 4:1. Preferably, in step S1, the loading treatment is carried out at 30-45°C for 30-60 minutes, and the material is stirred, turned or rolled during the loading treatment. Preferably, in step S1, after the loading treatment is completed, the material is dried at 40-60°C so that the moisture content of the resulting loaded composite deodorizing material is not higher than 10%.
[0018] Preferably, in step S2, when the amount of pregelatinized pea starch in the starch-based component is greater than 0 parts, 70% to 90% of the pregelatinized pea starch is added to the mixed base material based on a dry basis of 100%, and the remaining 10% to 30% of the pregelatinized pea starch is reserved for particle surface coating in step S4; when the amount of pregelatinized pea starch in the starch-based component is 0 parts, 5% to 15% of the natural pea starch is reserved for preparing the starch coating solution in step S4 based on a dry basis of 100%, and the remaining natural pea starch is added to the mixed base material. Preferably, in step S2, the natural pea starch and pea fiber used for mixing the base material are premixed first, and then the pregelatinized pea starch and the loaded composite deodorizing material used for mixing the base material are added and mixed to reduce the detachment of the composite deodorizing components from the surface of the porous pea starch during the long mixing process. Preferably, in step S2, the moisture content of the mixed base material is 10% to 15%; Preferably, in step S2, the mixing temperature of the mixed base material is not higher than 45°C.
[0019] Preferably, in step S3, the roller rotation speed of the roller granulation equipment is 10-60 r / min, the forming temperature is 70-95℃, and the roller pressing pressure is 8-40 MPa. Preferably, in step S3, the initial particle size of the cat litter is 1.5–4.0 mm; In the heating and roll forming process, by controlling the moisture content of the mixed base material, the rotation speed of the rollers, the forming temperature and the roll forming pressure, the mixed base material is compacted into granules, and the surface of the cat litter granules is compacted and thermomechanically modified. Under suitable conditions, at least part of the starch is gelatinized, thereby improving the bonding stability of the granule surface, while retaining space inside the granules for liquid penetration and the compound deodorizing components to play their role.
[0020] Preferably, in step S4, when pregelatinized pea starch is used to prepare the starch coating solution, the mass concentration of pregelatinized pea starch in the starch coating solution is 8% to 15%. Preferably, in step S4, when using natural pea starch to prepare the starch coating solution, the reserved natural pea starch is mixed with water to make the mass concentration of natural pea starch 8% to 15%, and then heated to 70 to 95°C and kept warm for 3 to 10 minutes to gelatinize at least part of the natural pea starch, thereby obtaining a starch coating solution with hydration and binding ability. Preferably, in step S4, the starch coating liquid is applied to the surface of the initial cat litter particles that are continuously turning or rolling by spraying; the starch coating liquid is applied in 2 to 4 times, and after each application, the particles are turned over for 2 to 10 minutes before the next application is carried out, so as to improve the uniformity of the coating layer and reduce particle adhesion.
[0021] Preferably, in step S5, the low-temperature drying temperature is 40-60°C, the drying time is 40-150 min, and the drying is carried out until the moisture content of the cat litter particles is 5%-12%; the dried cat litter particles are cooled to no higher than 35°C and then sieved.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects: This invention uses natural pea starch and porous pea starch as the base components of the starch-based component, and pregelatinized pea starch can be selectively added according to the product formulation. When used in conjunction with pea fiber, it forms a cat litter raw material system primarily composed of plant-derived materials. This helps reduce the amount of mineral materials used while considering the granule's water absorption, structural stability, and internal porosity. Natural pea starch serves as the main water absorbent and granule skeleton, while porous pea starch handles the loading and fixation of the composite deodorizing components. When the formulation contains pregelatinized pea starch, it further enhances the rapid hydration and wet adhesion of the granules upon contact with liquid.
[0023] This invention preloads composite deodorizing components onto the pores and surface of porous pea starch, then disperses the resulting loaded composite deodorizing material within cat litter granules. This improves the uniformity and stability of the composite deodorizing components in the cat litter, reducing agglomeration, shedding, and dust caused by direct mixing of fine powder deodorizing components. The invention employs a composite deodorizing system composed of β-cyclodextrin, persimmon tannin, and a citric acid-sodium citrate buffer component. This system utilizes the functional characteristics of different types of deodorizing components to comprehensively treat various odor substances produced by cat excrement, thereby enhancing the composite deodorizing ability and the duration of the deodorizing effect of the cat litter.
[0024] This invention incorporates pea fiber, which helps to regulate the internal structure and liquid permeability of cat litter granules, and improves granule toughness. The invention uses heating and roller pressing to granulate the mixed base material, causing compaction and thermomechanical modification of the cat litter granule surface. Under suitable conditions, at least some of the starch can be gelatinized, which improves the bonding stability and wear resistance of the granule surface, reduces dust generated by friction during transportation, dumping, and use, while preserving internal liquid permeability and deodorization space within the granules.
[0025] This invention reserves a portion of pea starch for surface hydration and binding coating after granulation, ensuring that the starch component with hydration and binding capabilities is primarily concentrated on the exterior of the cat litter granules. When the formula contains pregelatinized pea starch, the coating layer can be formed directly using the pregelatinized pea starch; when the formula does not contain pregelatinized pea starch, the reserved natural pea starch can be heated and gelatinized to form a coating liquid. The resulting surface coating layer helps to fix free fine powder on the granule surface and hydrates rapidly upon contact with the liquid, forming a wet bond between adjacent cat litter granules, thus achieving both low dust performance and rapid clumping performance.
[0026] This invention combines internal loading of composite deodorizing components, compaction and thermomechanical modification of the granule surface formed by roller pressing, and hydration and binding coating of pea starch on the surface. This allows the internal and external surfaces of the cat litter granules to perform different functions, which helps reduce interference between water absorption, clumping, deodorization, and dust reduction functions, thereby improving the overall performance of the cat litter. The loaded composite deodorizing material, granulated particle structure, and surface coating layer of this invention all use starch as the main functional carrier, which helps improve the compatibility between different raw materials, reduces the use of non-plant-derived binding materials, and gives the resulting cat litter better plant-derived properties, user comfort, and environmental adaptability. Attached Figure Description
[0027] Figure 1 PM10 net concentration-time variation curve during simulated dumping process of plant-derived pea starch deodorizing and dust-reducing cat litter; Figure 2Ammonia removal rate versus time curve after a single liquid addition for plant-derived pea starch deodorizing and dust-reducing cat litter; Figure 3 The removal rate of hydrogen sulfide by plant-derived pea starch-based deodorizing and dust-reducing cat litter over time is shown in the graph. Detailed Implementation
[0028] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Unless otherwise specified, the raw materials involved in the present invention are all purchased through conventional commercial channels. Experimental methods without specific conditions are conventional methods and conditions well known in the art, or according to the conditions recommended by the instrument manufacturer. The porous pea starch used in Examples 1 to 5 is the same batch of enzymatically hydrolyzed porous pea starch, with a median particle size D. 50 Its thickness is 30 μm, and its BET specific surface area is 2.5 m². 2 / g, with an oil absorption rate of 130%. Example
[0029] This embodiment provides a plant-derived pea starch deodorizing and low-dust cat litter; based on a dry basis total mass of 100 parts, its raw material composition is: 75 parts starch-based component, 22 parts pea fiber, and 3 parts compound deodorizing component.
[0030] Based on a total mass of 100 parts of starch-based components, the composition is: 72 parts of natural pea starch, 18 parts of pregelatinized pea starch, and 10 parts of porous pea starch.
[0031] Based on a total mass of 100 parts of the compound deodorizing components, its composition is: 50 parts of β-cyclodextrin, 20 parts of persimmon tannin, and 30 parts of citric acid-sodium citrate buffer component; the mass ratio of citric acid to sodium citrate in the buffer component is 1:0.5.
[0032] According to the above ratio, the mass ratio of porous pea starch to the compound deodorizing component is 1:0.4.
[0033] The preparation method of this embodiment includes the following steps: S1: Weigh the composite deodorizing component and porous pea starch according to the above ratio, mix the composite deodorizing component and water at a mass ratio of 1:2 to prepare a composite deodorizing dispersion; spray the composite deodorizing dispersion into the continuously stirred porous pea starch in batches, and load it at 30°C for 30 minutes; after the loading is completed, dry it at 40°C until the moisture content of the obtained material is 10%, and obtain the loaded composite deodorizing material after depolymerization; S2: Premix natural pea starch and pea fiber, then add 70% of the total mass of pregelatinized pea starch and the loaded composite deodorizing material obtained in step S1, and mix evenly; reserve the remaining 30% of pregelatinized pea starch for step S4; spray water into the initial mixture to adjust the moisture content of the mixture to 10%, and continue mixing at 25°C. The adjusted mixture should remain in a loose powder state and should not form wet lumps, soft materials or slurry. S3: The mixed base material is fed into the roller granulation equipment and granulated under the conditions of roller speed of 10r / min, molding temperature of 70℃ and roller pressing pressure of 8MPa to produce initial cat litter particles with a particle size of about 1.5mm. S4: Mix the pregelatinized pea starch reserved in step S2 with water to prepare a starch coating solution with a pregelatinized pea starch mass concentration of 15%. Spray the starch coating solution twice onto the surface of the initial cat litter particles that are continuously turned over. After each spraying, continue turning over for 2 minutes to obtain surface-coated particles. S5: Dry the surface-coated granules at 40℃ for 150 min until the granule moisture content is 12%; cool to no higher than 35℃ and then sieve to obtain plant-derived pea starch deodorizing and low-dust cat litter. Example
[0034] This embodiment provides a plant-derived pea starch deodorizing and low-dust cat litter; based on a dry basis total mass of 100 parts, its raw material composition is: 80 parts starch-based component, 15 parts pea fiber, and 5 parts compound deodorizing component.
[0035] Based on a total mass of 100 parts of starch-based components, the composition is: 75 parts of natural pea starch, 18 parts of pregelatinized pea starch, and 7 parts of porous pea starch.
[0036] Based on a total mass of 100 parts of the compound deodorizing components, its composition is: 55 parts of β-cyclodextrin, 25 parts of persimmon tannin, and 20 parts of citric acid-sodium citrate buffer component; the mass ratio of citric acid to sodium citrate in the buffer component is 1:1.
[0037] According to the above ratio, the mass ratio of porous pea starch to the compound deodorizing component is 1:0.89.
[0038] Weigh the composite deodorizing component and porous pea starch according to the above ratio, mix the composite deodorizing component with water at a mass ratio of 1:2.5 to prepare a composite deodorizing dispersion; spray the composite deodorizing dispersion into the porous pea starch in batches, stir and load at 34°C for 38 min; then dry at 45°C until the moisture content is 9%, and obtain the loaded composite deodorizing material after depolymerization; Natural pea starch and pea fiber are premixed, and then 75% of the total mass of pregelatinized pea starch and a load-bearing composite deodorizing material are added. The remaining 25% of the pregelatinized pea starch is reserved for surface coating. Water is sprayed to adjust the moisture content of the mixed base to 12%, and it is mixed evenly at 30°C to keep the mixed base in a loose state. The mixed base material is fed into a roller granulation equipment and granulated under the conditions of roller speed of 20 r / min, molding temperature of 75℃ and roller pressing pressure of 18 MPa to produce initial cat litter particles with a particle size of about 2.0 mm. The reserved pregelatinized pea starch was prepared into a starch coating solution with a mass concentration of 13%, and sprayed twice onto the surface of the initial cat litter granules that were continuously turned over. After each spraying, the granules were turned over for 4 minutes. The resulting surface-coated granules were dried at 45°C for 120 minutes until the granule moisture content was 10%. After cooling and sieving, plant-derived pea starch deodorizing and low-dust cat litter was obtained. Example
[0039] This embodiment provides a plant-derived pea starch deodorizing and dust-reducing cat litter; based on a dry basis total mass of 100 parts, its raw material composition is: 85 parts starch-based component, 11 parts pea fiber, and 4 parts compound deodorizing component.
[0040] Based on a total mass of 100 parts of starch-based components, the composition is: 80 parts of natural pea starch, 12 parts of pregelatinized pea starch, and 8 parts of porous pea starch.
[0041] Based on a total mass of 100 parts of the composite deodorizing components, its composition is: 60 parts of β-cyclodextrin, 20 parts of persimmon tannin, and 20 parts of citric acid-sodium citrate buffer component; the mass ratio of citric acid to sodium citrate in the buffer component is 1:1.5.
[0042] According to the above ratio, the mass ratio of porous pea starch to the compound deodorizing component is 1:0.59.
[0043] Weigh the composite deodorizing component and porous pea starch according to the above ratio, mix the composite deodorizing component with water at a mass ratio of 1:3 to prepare a composite deodorizing dispersion; spray the composite deodorizing dispersion into the porous pea starch in batches, and load it at 38°C for 45 min; then dry it at 50°C until the moisture content is 9%, and depolymerize to obtain the loaded composite deodorizing material. Natural pea starch and pea fiber are premixed, then 80% of the total mass of pregelatinized pea starch and a load-bearing composite deodorizing material are added, and the remaining 20% of the pregelatinized pea starch is reserved for surface coating; water is sprayed to adjust the moisture content of the mixed base to 14%, and the mixture is mixed evenly at 35°C. The mixed base material is fed into a roller granulation equipment and granulated under the conditions of roller speed of 30 r / min, molding temperature of 80℃ and roller pressing pressure of 25 MPa to produce initial cat litter granules with a particle size of about 2.5 mm. The reserved pregelatinized pea starch was prepared into a starch coating solution with a mass concentration of 11%, and sprayed three times onto the surface of the initial cat litter granules that were continuously turned over. After each spraying, the granules were turned over for 6 minutes. The resulting surface-coated granules were dried at 50°C for 90 minutes until the granule moisture content was 8%. After cooling and sieving, plant-derived pea starch deodorizing and low-dust cat litter was obtained. Example
[0044] This embodiment provides a plant-derived pea starch deodorizing and dust-reducing cat litter; based on a dry basis total mass of 100 parts, its raw material composition is: 90 parts starch-based component, 7 parts pea fiber, and 3 parts compound deodorizing component.
[0045] Based on a total mass of 100 parts of starch-based components, the composition is: 88 parts of natural pea starch, 7 parts of pregelatinized pea starch, and 5 parts of porous pea starch.
[0046] Based on a total mass of 100 parts of the compound deodorizing components, its composition is: 70 parts of β-cyclodextrin, 15 parts of persimmon tannin, and 15 parts of citric acid-sodium citrate buffer component; the mass ratio of citric acid to sodium citrate in the buffer component is 1:2.
[0047] According to the above ratio, the mass ratio of porous pea starch to the compound deodorizing component is 1:0.67.
[0048] Weigh the composite deodorizing component and porous pea starch according to the above ratio, mix the composite deodorizing component with water at a mass ratio of 1:3.5 to prepare a composite deodorizing dispersion; spray the composite deodorizing dispersion into the porous pea starch in batches, and load it at 42°C for 50 min; then dry it at 55°C until the moisture content is 8.5%, and depolymerize to obtain the loaded composite deodorizing material; Natural pea starch and pea fiber are premixed, then 85% of the total mass of pregelatinized pea starch and a load-bearing composite deodorizing material are added, and the remaining 15% of the pregelatinized pea starch is reserved for surface coating; water is sprayed to adjust the moisture content of the mixed base to 14%, and the mixture is mixed evenly at 40°C. The mixed base material is fed into a roller granulation equipment and granulated under the conditions of roller speed of 45 r / min, molding temperature of 90℃ and roller pressing pressure of 32 MPa to produce initial cat litter granules with a particle size of about 3.2 mm. The reserved pregelatinized pea starch was prepared into a starch coating solution with a mass concentration of 9.5%, and sprayed three times onto the surface of the initial cat litter granules that were continuously turned over. After each spraying, the granules were turned over for 8 minutes. The resulting surface-coated granules were dried at 55°C for 60 minutes until the granule moisture content was 6%. After cooling and sieving, plant-derived pea starch deodorizing and low-dust cat litter was obtained. Example
[0049] This embodiment provides a plant-derived pea starch deodorizing and low-dust cat litter; based on a dry basis total mass of 100 parts, its raw material composition is: 95 parts starch-based component, 2 parts pea fiber, and 3 parts compound deodorizing component.
[0050] Based on a total mass of 100 parts of starch-based components, the composition is as follows: 95 parts of natural pea starch, 0 parts of pregelatinized pea starch, and 5 parts of porous pea starch; wherein, 0 parts of pregelatinized pea starch means that no pregelatinized pea starch is added during the raw material feeding stage.
[0051] Based on a total mass of 100 parts of the composite deodorizing components, its composition is: 75 parts of β-cyclodextrin, 10 parts of persimmon tannin, and 15 parts of citric acid-sodium citrate buffer component; the mass ratio of citric acid to sodium citrate in the buffer component is 1:2.5.
[0052] According to the above ratio, the mass ratio of porous pea starch to the compound deodorizing component is 1:0.63.
[0053] Weigh the composite deodorizing component and porous pea starch according to the above ratio, mix the composite deodorizing component with water at a mass ratio of 1:4 to prepare a composite deodorizing dispersion; spray the composite deodorizing dispersion into the porous pea starch in batches, and load it at 45°C for 60 min; then dry it at 60°C until the moisture content is 8%, and depolymerize to obtain the loaded composite deodorizing material. 90% of the total mass of natural pea starch is premixed with pea fiber, and then a load-type composite deodorizing material is added. The remaining 10% of the natural pea starch is reserved for step S4. Water is sprayed to adjust the moisture content of the mixed base to 15%, and the mixture is mixed evenly at a temperature not exceeding 45°C to keep the mixed base in a loose state. The mixed base material is fed into a roller granulation equipment and granulated under the conditions of roller speed of 60 r / min, molding temperature of 95℃ and roller pressing pressure of 40 MPa to produce initial cat litter particles with a particle size of about 4.0 mm. The natural pea starch reserved in step S2 is mixed with water to prepare a starch dispersion with a natural pea starch mass concentration of 8%. The starch dispersion is heated to 95°C and kept warm for 10 minutes to gelatinize at least part of the natural pea starch, resulting in a starch coating liquid with hydration and binding ability. The starch coating liquid is sprayed four times onto the surface of the initial cat litter particles that are continuously turned over. After each spraying, the particles are turned over for another 10 minutes to obtain surface-coated particles. The obtained surface-coated granules were dried at 60℃ for 40 minutes until the granule moisture content was 5%; after cooling to no higher than 35℃, they were sieved to obtain plant-derived pea starch deodorizing and low-dust cat litter.
[0054] Comparative Example 1: The only difference between this comparative example and Example 3 is that the porous pea starch in the starch-based component is replaced by an equal mass of untreated pea starch; the remaining raw material amounts and preparation steps are the same as in Example 3. This comparative example is used to investigate the effect of the pore structure of porous pea starch on the loading stability, dispersion uniformity, deodorization retention, and cat litter dust performance of the composite deodorizing component.
[0055] Comparative Example 2: The raw material composition of this comparative example is exactly the same as that of Example 3, except that the composite deodorizing component is not pre-loaded into porous pea starch. During preparation, the porous pea starch was spray-treated with the same mass of water as in step S1 of Example 3, stirred at 38°C for 45 min, and then dried at 50°C to the same moisture content as the loaded composite deodorizing material of Example 3 and depolymerized. β-cyclodextrin, persimmon tannin, citric acid, and sodium citrate were directly added to the initial mixture in step S2. The remaining raw material amounts and preparation steps were the same as in Example 3. This comparative example was used to investigate the effect of pre-loading the composite deodorizing component into the pores and surface of porous pea starch on the fixation stability, powder shedding, initial deodorizing performance, and sustained deodorizing performance of the composite deodorizing component, compared to directly mixing porous pea starch and the composite deodorizing component.
[0056] Comparative Example 3: The raw material composition of this comparative example is exactly the same as that of Example 3, except that the initial cat litter granules obtained by granulation are not coated with pea starch surface hydration adhesive coating. During preparation, in step S2, all pregelatinized pea starch is added to the mixed base; in step S4, no pregelatinized pea starch is added, but water with the same water content as the starch coating solution in Example 3 is sprayed onto the continuously agitated surface of the initial cat litter granules, maintaining the same number of sprays and the same agitation time after each spray; the remaining raw material amounts and preparation conditions are the same as in Example 3. This comparative example is used to investigate the effects of pea starch surface hydration adhesive coating on the fixation of fine powder on the granule surface, granule abrasion resistance, dust generation during use, hydration rate after liquid absorption, and wet mass integrity.
[0057] Comparative Example 4: The raw material composition of this comparative example is exactly the same as that of Example 3, except that the granulation temperature in step S3 is 60°C. During preparation, the roller speed of the roller granulator in step S3 remains 30 r / min, and the roller pressing pressure remains 25 MPa. Only the molding temperature is adjusted from 80°C in Example 3 to 60°C. The remaining raw material amounts, load treatment, moisture content of the mixed base material, surface coating, and low-temperature drying conditions are the same as in Example 3. This comparative example is used to investigate the effects of granulation temperature and the resulting particle surface compaction and thermomechanical modification on particle bonding stability, wear resistance, dust generation, and water absorption and agglomeration properties.
[0058] Performance Testing: To verify the improved effects of the plant-derived pea starch deodorizing and low-dust cat litter of the present invention on water absorption and clumping, wet clumping integrity, particle abrasion resistance and low dust, and continuous deodorization, performance tests were conducted on the cat litters obtained in Examples 1-5 and Comparative Examples 1-4. Example 5 was used to further verify the comprehensive performance of the cat litter obtained by using natural pea starch after heating and gelatinization for surface hydration and binding coating without adding pregelatinized pea starch to the raw materials. Before testing, each group of cat litter samples was placed in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 24 hours to equilibrate. Three parallel samples were set for each test, and the test results were taken as the arithmetic mean.
[0059] Water absorption and clumping performance test: Referring to the test principle of T / SDPIA 02-2023 "Method for Determining the Water Absorption Characteristics of Cat Litter", the water absorption time and wet clump integrity rate of the cat litters obtained in Examples 1-5 and Comparative Examples 1-4 were tested. 1500g of cat litter samples were weighed and spread evenly in a sample pan 300mm long, 200mm wide, and 100mm deep, making the litter layer thickness 70mm. The sample surface was smoothed but not compacted. A 1.0% sodium chloride aqueous solution was prepared and its temperature adjusted to 38±1℃. 20mL of the sodium chloride aqueous solution was measured using a dripping device, with the drip nozzle 30mm from the center of the cat litter surface. The sodium chloride aqueous solution was evenly dripped onto the cat litter surface over 30s. The time required for the visible free liquid on the cat litter surface to completely disappear was recorded from the start of the dripping of the sodium chloride aqueous solution; this time was taken as the water absorption time. After adding the litter, let it stand for 60 seconds. Then, use a litter scoop of the same size to completely remove the formed wet clump and weigh it, recording the initial mass as m0. Next, let the wet clump fall freely from a height of 500mm onto a horizontal stainless steel plate, repeating this process 5 times. Collect the largest intact wet clump after each drop and weigh it, recording its mass as m1. The wet clump integrity rate is calculated using the following formula: Wet clump integrity rate = m1 / m0 × 100%. A shorter absorption time indicates faster absorption and hydration of the litter after contact with the liquid; a higher wet clump integrity rate indicates better adhesion stability and scoopability of the formed wet clump. Performance test results are shown in Table 1.
[0060] Particle abrasion and pulverization performance test: Referring to the evaluation criteria for cat litter powder content and pulverization rate in T / BYXT 084-2024, the initial powder content and pulverization rate of the cat litters obtained in Examples 1-5 and Comparative Examples 1-4 were tested. 500g of unsieving cat litter sample was weighed and recorded as m2. The sample was placed on a standard sieve with a 0.50mm aperture and sieved for 60s at a vibration frequency of 180 times / min. The mass of fine powder passing through the standard sieve was weighed and recorded as m3. The initial powder content was calculated using the following formula: Initial powder content = m3 / m2 × 100%. The lower the initial powder content, the less free fine powder remains after drying, cooling, and sieving.
[0061] Pulverization rate: Take another 500g of cat litter sample after pre-screening with a 0.50mm standard sieve to remove dust, and record it as m4. Place it into a 5L closed cylindrical durability testing device. Control the testing device to rotate at 50r / min for 10min, so that the cat litter particles continuously tumble and collide with each other inside the cylinder. After the test, take out all samples, and use a 0.50mm standard sieve to sieve for 60s under the condition of vibrating sieve frequency of 180 times / min. Weigh the mass of the newly formed fine powder that passes through the standard sieve, and record it as m5. The pulverization rate is calculated by the following formula: Pulverization rate = m5 / m4 × 100%. The lower the pulverization rate, the better the wear resistance stability of the cat litter particles during simulated transportation, dumping, and cat scratching. The test results of initial dust content and pulverization rate are shown in Table 2.
[0062] Simulated Dust Generation Dynamic Test During Pour-Out: To evaluate the generation and settling of airborne dust during actual cat litter pouring, simulated dust generation dynamic tests were conducted on the cat litter obtained in Example 3, Comparative Example 2, Comparative Example 3, and Comparative Example 4. The tests used litter with an internal volume of 1 m³. 3A sealed test chamber was used, with a litter box measuring 300mm long, 200mm wide, and 100mm deep placed at the bottom. The sampling port of a laser dust detector was fixed 200mm directly above the center of the litter box, with the sampling interval set to 1 second. Before the test, the test chamber was sealed, and the PM10 concentration was continuously recorded for 60 seconds, with the average concentration during this period used as the background concentration. 1000g of litter sample was weighed and poured into the litter box from 500mm directly above the center at a rate of 100g / s. The dust detector was activated simultaneously with the pouring, continuously recording the PM10 concentration for 180 seconds after the pouring began. The net PM10 concentration at each time point was calculated using the following formula: Net PM10 concentration = Measured PM10 concentration - Background PM10 concentration. After each test, the test chamber was thoroughly ventilated and cleaned. The next set of tests was conducted only after the PM10 concentration inside the chamber returned to the background level. Plot a PM10 net concentration-time curve with the time from the start of litter disposal on the x-axis and the net PM10 concentration on the y-axis. A lower peak and a faster rate of decline after the peak indicate less airborne dust generated during litter disposal and a faster dust settling rate. See the PM10 net concentration-time curve below. Figure 1 .
[0063] Single-addition dynamic deodorization performance test: Referring to the test principle of ammonia deodorization performance of cat litter in T / CIQA 11-2020, the single-addition dynamic deodorization performance of the cat litter obtained in Example 3, Comparative Example 1, and Comparative Example 2 was tested. A transparent, sealed test chamber with internal dimensions of 300mm (length), 200mm (width), and 200mm (height) was used. A sample tray with dimensions of 150mm (length), 100mm (width), and 50mm (depth) was placed at the bottom of the test chamber. 300g of cat litter was added to the sample tray, and the sample surface was smoothed without compaction. The sampling probe of the ammonia detector was fixed at a horizontal distance of 100mm from the center of the sample tray and 50mm from the surface of the cat litter. The temperature inside the test chamber was controlled at 23±2℃. Ammonia solution with a mass concentration of 0.5% was prepared. 20mL of ammonia solution was measured using a pipette and evenly dripped onto the surface of the cat litter sample within 30 seconds. The test chamber was immediately sealed after the dripping was completed. The ammonia concentration in the test chamber was measured at 3 min, 10 min, 30 min, 60 min, 180 min, 360 min, and 1440 min under sealed conditions. The blank test used the same test chamber, sample tray, ammonia volume, and test conditions. Inert glass beads with the same bulk volume as 300g of cat litter were added to the sample tray to reduce the difference in effective gas volume caused by different sample volumes. The ammonia concentration in the blank test was measured at each time point. The ammonia removal rate of the cat litter at time t was calculated using the following formula: Ammonia removal rate = (Ammonia concentration in the blank test at time t - Ammonia concentration after adding the cat litter sample at time t) / Ammonia concentration in the blank test at time t × 100%. The first part of the curve is used to evaluate the initial deodorization rate of the cat litter, and the middle and later parts of the curve are used to evaluate the sustained deodorization performance of the composite deodorizing components. After each test, the test chamber, sample tray, and sampling probe were cleaned, and the test chamber was thoroughly ventilated. The next test was conducted after the ammonia concentration returned to below the detection limit. The ammonia removal rate-time curve is shown below. Figure 2 .
[0064] To simulate the ability of cat litter to handle ammonia odor from urine under continuous use, repeated liquid addition deodorization retention performance tests were conducted on the cat litters obtained in Examples 1-5, Comparative Examples 1 and 2. The sample volume, test chamber dimensions, sample tray dimensions, ammonia detector location, and ambient temperature remained consistent with the single-liquid addition dynamic deodorization performance test. In the first test cycle, 20 mL of 0.5% ammonia solution was evenly added to the surface of a 300 g cat litter sample. The test chamber was immediately sealed after addition, and the ammonia concentration was measured after 30 minutes of sealing. After measurement, the test chamber was opened for ventilation to restore the ammonia concentration to below the detection limit, and the cat litter sample remained in the sample tray. The second test cycle was conducted 24 hours later. Again, 20 mL of 0.5% ammonia solution was evenly added to the surface of the same cat litter sample, and the ammonia concentration was measured after 30 minutes of sealing, following the same method as the first test cycle. A third test cycle was conducted after a 24-hour interval, with the same method used for the third ammonia addition and concentration measurement. The blank test used the same test chamber, sample tray, ammonia volume, addition interval, and ventilation conditions; no cat litter was added to the sample tray (inert glass beads with the same bulk volume as 300g of cat litter were added). Based on the blank ammonia concentration and sample ammonia concentration for each test cycle, the ammonia removal rate was calculated 30 minutes after the first, second, and third additions. The odor retention rate for the third cycle was calculated using the following formula: Odor retention rate for the third cycle = Ammonia removal rate after the third addition / Ammonia removal rate after the first addition × 100%. A higher odor retention rate for the third cycle indicates that the cat litter maintains good deodorizing ability after continuously absorbing excrement. The results of the repeated addition odor retention performance test are shown in Table 3.
[0065] Hydrogen sulfide removal performance test: To evaluate the ability of the cat litter of the present invention to treat sulfur-containing odor substances, the hydrogen sulfide removal performance of the cat litter obtained in Example 3, Comparative Example 1, and Comparative Example 2 was tested. To directly verify the effect of persimmon tannin on the treatment of sulfur-containing odor substances, a persimmon tannin-deficient control was set up. The persimmon tannin-deficient control was based on Example 3, omitting the persimmon tannin in the compound deodorizing component and supplementing it with natural pea starch on an equal dry basis. The composition of other raw materials and preparation conditions were the same as in Example 3. A 20L airtight test chamber was used. A sample tray with a length of 200mm, a width of 150mm, and a depth of 50mm was placed at the bottom of the test chamber. 200g of cat litter was added to the sample tray, and the surface of the cat litter was scraped flat without compaction. A 1000ppm hydrogen sulfide-nitrogen standard gas, which had been certified by metrology, was injected into the test chamber through a mass flow controller and diluted with sulfur-free air to achieve an initial hydrogen sulfide concentration of 10.0±0.5ppm in the test chamber. A small circulating fan was installed inside the test chamber and ran for 60 seconds after gas injection to ensure uniform mixing. The fan was then turned off, and timing began. An electrochemical hydrogen sulfide detector calibrated with standard gases was used to measure the hydrogen sulfide concentration in the test chamber at 0, 5, 15, 30, and 60 minutes. For the blank test, inert glass beads with the same volume as 200g of cat litter were added to the sample pan. All other test conditions were the same as in the cat litter test, used to correct for hydrogen sulfide concentration variations caused by adsorption on the test chamber walls, gas leakage, and natural decay. The hydrogen sulfide removal rate of the cat litter at time t was calculated using the following formula: Hydrogen sulfide removal rate = (Hydrogen sulfide concentration in the blank test at time t - Hydrogen sulfide concentration after adding the cat litter sample at time t) / Hydrogen sulfide concentration in the blank test at time t × 100%. Three independent parallel tests were set up for each group of tests. After each test, the gas in the test chamber was introduced into an alkaline oxidation absorption liquid for treatment. The next test was conducted only after the hydrogen sulfide concentration in the test chamber was below the detection limit. Test results are shown below. Figure 3 .
[0066] In summary, the test results are shown in Tables 1 to 3 and... Figures 1-3 Table 1 shows the water absorption and clumping performance test results of plant-derived pea starch deodorizing and dust-reducing cat litter; Table 2 shows the initial powder content and powdering rate test results of plant-derived pea starch deodorizing and dust-reducing cat litter; Table 3 shows the deodorization retention performance test results of plant-derived pea starch deodorizing and dust-reducing cat litter after repeated liquid addition. Figure 1 The PM10 net concentration-time change curve during the simulated cat litter dumping process; Figure 2 The curve shows the ammonia removal rate over time after a single addition of liquid to the cat litter. Figure 3 This is the hydrogen sulfide removal rate versus time curve.
[0067] Table 1. Test results of water absorption and clumping performance of plant-derived pea starch deodorizing and dust-reducing cat litter.
[0068] Table 2. Test results of initial dust content and dusting rate of plant-derived pea starch deodorizing and dust-reducing cat litter.
[0069] Table 3. Test results of odor retention performance of plant-derived pea starch deodorizing and dust-reducing cat litter with repeated dosing.
[0070] As shown in Table 1, Examples 1-5 all exhibited good liquid absorption and agglomeration performance. Example 2 had the shortest liquid absorption time (37 seconds), while Example 3 had the highest wet agglomeration integrity rate (96.6%). The higher proportion and smaller particle size of pregelatinized pea starch in Examples 1 and 2 facilitated rapid liquid contact and hydration of the surface starch. Example 3 had a more suitable match between the starch-based component, pea fiber, surface coating, and granulation conditions, resulting in better wet agglomeration stability. With increasing starch-based component content and rolling pressure, the particle structure of Examples 4 and 5 became relatively dense, leading to a decrease in liquid absorption speed. Notably, although Example 5 did not add pregelatinized pea starch, it used natural pea starch that had been gelatinized by heating for surface coating, and its wet agglomeration integrity rate still reached 92.8%, indicating that this coating method could maintain good agglomeration performance. In contrast, after removing the surface hydration and binding coating in Comparative Example 3, the liquid absorption time was extended to 61s, and the wet agglomeration integrity rate dropped to 79.8%. Although the liquid absorption was faster after lowering the granulation temperature in Comparative Example 4, the wet agglomeration integrity rate was only 83.2%, indicating that rapid liquid absorption is not equivalent to stable agglomeration, and suitable particle structure and surface hydration and binding ability are more important.
[0071] From Table 2 and Figure 1 It can be seen that Example 3 had the lowest initial powder content and pulverization rate, at 0.18% and 0.68% respectively, and its PM10 concentration during the simulated pouring process was also significantly lower than that of the comparative examples. This indicates that suitable roller granulation can improve the bonding stability of the particle surface, and the surface coating of pea starch after granulation further helps to fix free fine powder. In Example 5, after in-situ gelatinization and coating with natural pea starch, the initial powder content was still only 0.27%, indicating that this process also has a good dust-reducing effect. In Comparative Example 2, the amount of free functional powder increased after the pre-loading was removed; in Comparative Example 3, the fine powder on the particle surface was difficult to fix after the surface coating was removed; and in Comparative Example 4, the particle bonding stability decreased due to the low molding temperature. Therefore, Figure 1 Overall, Example 3 showed the lowest dynamic dust emission, while Comparative Example 3 showed the highest, consistent with the results of dust content and pulverization rate in Table 2.
[0072] From Table 3 and Figure 2It can be seen that the dosage of the composite deodorizing components has a certain impact on the initial ammonia removal capacity, while the porous carrier and pre-loading state are more important for continuous deodorization performance. Example 2 showed the highest ammonia removal rate after the first liquid addition, at 94.1%; Example 3 maintained good deodorization capacity even after continuous liquid addition, with an ammonia removal rate of 84.5% after the third addition, and a cyclic deodorization retention rate of 91.0%. Example 5 still achieved a cyclic deodorization retention rate of 87.5%, indicating that not adding pregelatinized pea starch does not significantly affect the internally loaded deodorizing system. Figure 2 Further analysis shows that Comparative Example 2 had a faster response in the initial stage, but the decay was most significant over time. Its deodorization retention rate in the third cycle was only 48.3%, indicating that preloading the composite deodorizing components into porous pea starch is beneficial to improving the stability and sustainability of the deodorization effect.
[0073] Depend on Figure 3 It can be seen that the hydrogen sulfide removal rate of each group increased with the extension of contact time and gradually tended to stabilize. At 60 min, the hydrogen sulfide removal rate of Example 3 reached 88.7%, which was higher than 75.3% of Comparative Example 2 and 65.7% of Comparative Example 1, indicating that the porous carrier and pre-loading treatment are beneficial to improving the dispersion and effective utilization of deodorizing components. The removal rate of the control without persimmon tannin was only 47.5%, indicating that persimmon tannin plays an important role in the adsorption and fixation of sulfur-containing odor substances. (See Table 3 for details.) Figure 2 and Figure 3 It can be seen that the composite deodorization system of the present invention can take into account both ammonia and sulfur-containing odors, and achieve a relatively stable and continuous deodorization effect through porous loading.
[0074] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the claims.
Claims
1. A plant-derived pea starch deodorizing and low-dust cat litter, characterized in that, Its composition includes the following raw materials: 75-95 parts of starch-based component; 2-22 parts of pea fiber and 3-5 parts of compound deodorizing component; the content of each raw material is selected within the above range, and the sum of the mass parts of the starch-based component, pea fiber and compound deodorizing component is 100 parts; the starch-based component includes natural pea starch and porous pea starch; the compound deodorizing component is composed of β-cyclodextrin, persimmon tannin and citric acid-sodium citrate buffer component.
2. The plant-derived pea starch deodorizing and low-dust cat litter according to claim 1, characterized in that, Its composition includes: 72-95 parts of natural pea starch; 0-18 parts of pregelatinized pea starch and 5-10 parts of porous pea starch; the sum of the mass parts of the natural pea starch, pregelatinized pea starch and porous pea starch is 100 parts.
3. The plant-derived pea starch deodorizing and low-dust cat litter according to claim 1, characterized in that, Based on a total mass of 100 parts, the composite deodorizing component comprises: 50-75 parts of β-cyclodextrin; 10-25 parts of persimmon tannin; and 15-30 parts of a citric acid-sodium citrate buffer component; the sum of the mass parts of the β-cyclodextrin, persimmon tannin, and citric acid-sodium citrate buffer component is 100 parts; in the citric acid-sodium citrate buffer component, the mass ratio of citric acid to sodium citrate is 1:0.5-2.
5.
4. The plant-derived pea starch deodorizing and low-dust cat litter according to claim 1, characterized in that, The mass ratio of the porous pea starch to the composite deodorizing component is 1:0.4 to 1.
0.
5. A method for preparing plant-derived pea starch deodorizing and low-dust cat litter according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1: β-cyclodextrin, persimmon tannin and citric acid-sodium citrate buffer components are mixed with water to prepare a composite deodorizing dispersion. The composite deodorizing dispersion is added to porous pea starch for loading treatment, dried and depolymerized to obtain a loaded composite deodorizing material. S2: When the amount of pregelatinized pea starch in the starch-based component is greater than 0 parts, a portion of the pregelatinized pea starch is reserved for step S4; when the amount of the pregelatinized pea starch is 0 parts, a portion of the natural pea starch is reserved for step S4; the remaining starch raw materials except for the reserved portion are mixed with pea fiber and the loaded composite deodorizing material, and the moisture content is adjusted to obtain a mixed base material for granulation; S3: The mixed base material is fed into a roller granulator and granulated under heating and roller pressure to obtain initial cat litter particles; S4: Prepare a starch coating solution from the pea starch reserved in step S2 and apply it to the surface of the initial cat litter particles; when the reserved pea starch is natural pea starch, heat and gelatinize its aqueous dispersion system to prepare the starch coating solution. S5: The coated particles are dried at low temperature, cooled and sieved to obtain the plant-derived pea starch deodorizing and low-dust cat litter.
6. A method for preparing plant-derived pea starch deodorizing and low-dust cat litter according to claim 5, characterized in that, In step S2, when the amount of pregelatinized pea starch is greater than 0 parts, 70% to 90% of the pregelatinized pea starch is added to the mixed base material based on a dry basis of 100%, and the remaining 10% to 30% is reserved for the particle surface coating in step S4; when the amount of pregelatinized pea starch is 0 parts, 5% to 15% of the natural pea starch is reserved for the preparation of starch coating liquid in step S4 based on a dry basis of 100%, and the remaining natural pea starch is added to the mixed base material.
7. A method for preparing plant-derived pea starch deodorizing and low-dust cat litter according to claim 5, characterized in that, In step S2, the moisture content of the mixed base material is 10% to 15%; the mixing temperature of the mixed base material is not higher than 45°C.
8. A method for preparing plant-derived pea starch deodorizing and low-dust cat litter according to claim 5, characterized in that, In step S3, the rotation speed of the rollers in the roller granulation equipment is 10-60 r / min; the forming temperature is 70-95℃; the roller pressing pressure is 8-40 MPa; and the initial particle size of the cat litter is 1.5-4.0 mm.
9. A method for preparing plant-derived pea starch deodorizing and low-dust cat litter according to claim 5, characterized in that, In step S4, when the starch coating solution is prepared using pregelatinized pea starch, the mass concentration of pregelatinized pea starch in the starch coating solution is 8%–15%; when the starch coating solution is prepared using natural pea starch, the mass concentration of natural pea starch in the starch coating solution is 8%–15%, and the dispersion system formed by natural pea starch and water is heated to 70–95°C and kept at that temperature for 3–10 minutes to gelatinize at least part of the natural pea starch; the starch coating solution is applied in 2–4 applications, and after each application, the particles are agitated for 2–10 minutes before the next application.
10. A method for preparing plant-derived pea starch deodorizing and low-dust cat litter according to claim 5, characterized in that, In step S5, the low-temperature drying temperature is 40-60℃, the drying time is 40-150 min, and the drying is carried out until the moisture content of the cat litter particles is 5%-12%; the dried cat litter particles are cooled to no higher than 35℃ and then sieved.
